ERP-Driven Vendor Management: Unlocking Efficiency, Transparency, and Procurement - Desi Ramananda Kishore Katuri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The article explores the transformative impact of Enterprise Resource Planning (ERP) systems on vendor management across various industries. It examines how organizations shift from traditional, fragmented approaches to integrated, digital solutions that enhance operational efficiency and reduce risks. The article analyzes the evolution of vendor management practices, highlighting key benefits in workflow automation, data-driven decision-making, and compliance management. It investigates implementation challenges and provides practical solutions for change management, data quality assurance, and system integration. Furthermore, it discusses emerging trends in ERP vendor management, including artificial intelligence applications, blockchain integration, and advanced analytics capabilities. It demonstrates that ERP systems are a cornerstone for modern vendor management, enabling organizations to significantly improve operational efficiency, cost reduction, and strategic supplier relationships.
Keywords: Enterprise Resource Planning (ERP); Vendor Management Automation; Digital Supply Chain Integration; Compliance Risk Management; Business Process Optimization; Procurement